THE IMPACT OF MARKETING INNOVATION IN ENHANCING CUSTOMER LOYALTY: A CASE STUDY OF CUSTOMERS OF THE INSTITUTION "MOBILIS" - BOUIRA AGENCY (International Journal of Innovative Technologies in Economy, 2025)
This study aims at identifying the impact of marketing innovation on customer loyalty. To achieve this objective, the descriptive-analytical approach was used, by administering a questionnaire as the primary tool for data collection. The researchers selected randomly a sample of 100 customers of the Mobilis institution. Data processing and analysis were conducted using the Statistical Package for the Social Sciences (SPSS). The findings revealed a statistically significant relationship between marketing innovation and customer loyalty through its impact on the four dimensions of loyalty which are trust, complaint behavior, and word of mouth. The correlation coefficient for the five dimensions was similar, as was their explanatory power.